Examining the Influence of Gadget Dependence, Emotional Intelligence, and Social Control on Students' Religiosity Characteristics - Saputri, Syalsa Nur; Shodiq, Sadam Fajar (Jurnal Paedagogy, 2026)
This study aims to examine the impact of gadget dependence, emotional intelligence, and social control on students’ religious character. The study employed a quantitative approach using a Structural Equation Modeling design based on Partial Least Squares (PLS-SEM). Data were collected through a five-point Likert-scale questionnaire administered to a randomly selected sample of 350 senior high school students in Yogyakarta. The results indicate that gadget dependence has a significant negative effect on students’ religious character (β = −0.41, p < 0.001), while emotional intelligence (β = 0.37, p < 0.001) and social control (β = 0.29, p < 0.01) have significant positive effects. The structural model demonstrates strong explanatory power, with an R² value of 0.879, indicating that these variables collectively explain 87.9% of the variance in students’ religious character. These findings suggest that the development of students’ religious character in the digital era is influenced not only by cognitive factors but also by emotional regulation and social supervision. Therefore, strengthening digital literacy, providing emotional regulation training, and fostering collaboration among schools, families, and religious communities are essential strategies for cultivating adaptive religiosity grounded in moral and religious values.